Correlation between Prostate Volume and Intravesical Prostate Protrusion to Bladder Detrusor Muscle Thickness in Patients with Benign Prostate Enlargement by Transabdominal Ultrasound Examination in Banjar Jagatamu, Meliling, Kerambitan, Tabanan 2024 - Ni Made Putri Suastari; Ni Made Widya Mahayani; Dewa Komang Agung Hersya Paritranaya Dinata (Al Makki Health Informatics Journal, 2025)
Benign prostate enlargement (BPE) is a common degenerative condition in elderly men, often leading to lower urinary tract symptoms (LUTS) such as urgency, frequent urination, and incomplete bladder emptying. This study investigates the correlation between prostate volume, intravesical prostate protrusion (IPP), and bladder detrusor muscle thickness in patients with BPE using transabdominal ultrasonography. Conducted in Banjar Jagatamu, Meliling Village, Tabanan Regency, the study employed a cross-sectional design with 71 participants aged 60 years and older. Inclusion criteria required an International Prostate Symptom Score (IPSS) ≥ 8 or prostate volume > 20 mL. The results revealed a significant correlation between prostate volume and bladder detrusor muscle thickness (r = 0.665, p < 0.001) and between IPP and detrusor thickness (r = 0.806, p < 0.001). These findings highlight the utility of ultrasonography in assessing structural changes caused by chronic urinary obstruction. The study provides valuable insights into the role of prostate volume and IPP as predictive markers for bladder remodeling in BPE patients. By focusing on a rural population, this research emphasizes the need for accessible diagnostic tools to improve early detection and management of BPE, ultimately enhancing patient outcomes in underserved communities.